Effects of a 12-week gait retraining program combined with foot core exercise on morphology, muscle strength, and kinematics of the arch: A randomized controlled trial - Shen, Bin; Zhang, Shen; Cui, Kedong; Zhang, Xini; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: This study aims to explore the effects of a 12-week gait retraining program combined with foot core exercise on arch morphology, arch muscles strength, and arch kinematics. Methods: A total of 26 male recreational runners with normal arch structure who used rear-foot running strike (RFS) were divided into the intervention group (INT group) and control group (CON group) (n = 13 in each group). The INT group performed a 12-week forefoot strike (FFS) training combined with foot core exercises. The CON group did not change the original exercise habit. Before and after the intervention, the arch morphology, as well as the strength of hallux flexion, lesser toe flexion, and the metatarsophalangeal joint (MPJ) flexors were measured in a static position, and changes in the arch kinematics during RFS and FFS running were explored. Results: After a 12-week intervention, 1) the normalized navicular height increased significantly in the INT group by 5.1% (p = 0.027, Cohen’s d = 0.55); 2) the hallux absolute flexion and relative flexion of the INT group increased significantly by 20.5% and 21.7%, respectively (p = 0.001, Cohen’s d = 0.59; p = 0.001, Cohen’s d = 0.73), the absolute and relative strength of the MPJ flexors of the INT group were significantly improved by 30.7% and 32.5%, respectively (p = 0.006, Cohen’s d = 0.94; p = 0.006, Cohen’s d = 0.96); 3) and during RFS, the maximum arch angle of the INT group declined significantly by 5.1% (p < 0.001, Cohen’s d = 1.49), the arch height at touchdown increased significantly in the INT group by 32.1% (p < 0.001, Cohen’s d = 1.98). Conclusion: The 12-week gait retraining program combined with foot core exercise improved the arch in both static and dynamic positions with a moderate to large effect size, demonstrating the superiority of this combined intervention over the standalone interventions. Thus, runners with weak arch muscles are encouraged to use this combined intervention as an approach to enhance the arch.